Physical Activity Level of Students with Disabilities during COVID-19 Pandemic - Erick Burhaein; Beltasar Tarigan; Dian Budiana; Yudy Hendrayana; Diajeng Tyas Pinru Phytanza (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
Physical activity is one of the vital components of students with disabilities during the COVID-19 pandemic, which is endemic in various countries, including Indonesia. The purpose of the study was to determine the level of physical activity of students with disabilities during the COVID-19 pandemic. Participants of this study were 17 students with disabilities (intellectual disability, hearing impairment, speech impairment) aged 8-14 years. This research used a quantitative descriptive research method. The tool used was the Children's Physical Activity Questionnaire (PAQ-C) distributed through Google Forms. Data analysis included quantitative descriptive statistics analysis and the analytical need testing using IBM SPSS 24 applications. The results showed that the physical activity of students with disabilities during the COVID-19 pandemic was mostly distributed in the low category, nine students (50%). This study implied that students should maintain and increase physical activity by doing light physical activity at least 30 minutes a day and maintaining immunity by eating nutritious foods such as vitamins, fruits, vegetables, and healthy foods to prevent the spread of the COVID-19 virus. It will be interesting to study adaptive learning more deeply during pandemics in a broad scope in Indonesia for further research.